Heads Up: Communication Is Key in School Nurses' Preparedness for Facilitating "Return to Learn" Following Concussion. (March 2016) - Wing, Robyn; Amanullah, Siraj; Jacobs, Elizabeth; Clark, Melissa A.; Merritt, Chris
Background . Recent literature advocates for a school academic team, including school nurses, to support concussed students' return to the classroom. This study aimed to assess the current understanding and practices of a sample of school nurses regarding the concept of "return to learn" in concussed students. Methods . Cross-sectional survey of New England school nurses. Results . The greatest barrier to the school nurses' functioning within the academic rehabilitation team for students with concussion was "inadequate communication with the provider that diagnosed the concussion" (73%). Of the 151 school nurses surveyed, 19% felt that they did not have the training necessary for this role. Other barriers included "inadequate concussion training" (38%) and "inadequate time necessary to care for a student with concussion" (30%). Conclusions . By identifying specific gaps in knowledge and challenges at the school level, these results inform interdisciplinary medical teams about the importance of educating and facilitating effective "return to learn" academic plans.